Mineralogical zoning with X-ray difraction for the optimization of metallurgical treatment in the Toromocho Deposit - Flores Barrón, Ronald Eugenio (2020)
The Toromocho Deposit is a Porphyry Skarn deposit with an extension of 5 km by 6 km, geologically it is made up of volcanic rocks from Mitú and limestone from Pucara and tertiary intrusives. The mineralization is mainly due to veins that cross the entire Morococha district from East to West, which are filled with Pb, Zn and Ag Zinc mantles minerals located in the limestones and in a disseminated form, also located in the limestones and in the Volcanic-limestone-intrusive contacts and also scattered pyritic bodies with copper mineralization. Regarding its mineralization, it is very complex finding veins, mantles, stock work, scattered bodies, finding minerals that greatly affect metallurgical treatment such as arsenic. The results of the XRD studies allow us to characterize the existing minerals in the deposit, from the contaminating minerals to be able to perform a good blending, control talc, fluorine, magnesium, zinc, etc. The higher the talc content in CMC, the more effective it is with naturally buoyant bargains to achieve a minimum degree of 20%. It requires 700g / l of CMC. According to agreement with the metallurgy, planning and geology area, we came to terms of not considering some penalizable minerals such as fluorine, because in the central part of the deposit there is high fluorine as well as a high degree of copper, which allows blending. to be able to raise the copper grade, but in the metallurgical plant the molybdenum plant process has to be activated to be able to clean the mineral with high fluorine and talc with the addition of NaSH.